PENGARUH PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING TERHADAP HASIL BELAJAR BIOLOGI SISWA SMS ISLAM TERPADU AL-FITYAN GOWA - Husniyati Yahya (Jurnal Biotek, 2017)
The Influence of the Implementation of Quantum Teaching Learning Model Towards Biology Learning Result on Eksrection System of Grade XI Students at SMA Islam Terpadu Al-Fityan in Gowa. Quantum teaching learning model is a designed leaning model to further enable students in the learning process. This quantum teaching gives birth to a design framework that TANDUR is an (Abbeviation f grow, natural, named, demonstrate, repeat and celebrate). The study aints at examining the influence of the implementation of quantum teaching model towards student learning result in learning Biology. The stdudy is a quasi experiment. e population of the study was grade XI IPA students of the second semester of academy year 2016/2017 at SMA IT Al-Fityan Gowa. Samples where taken b employing random class. The result of the study reveal that the implementation of quantum teaching model gives significant influence towards student learning Biology result.